Синтез реагентів на основі 7-заміщених 3-тіазолілкумаринів для ковалентного мічення олігонуклеотидів - Кузів, Я.Б.; Іщенко, В.В.; Хиля, В.П.; Дубей, І.Я. (Інститут молекулярної біології і генетики НАН України, 2008)
Описано синтез карбоксильних похідних флуоресцентних зондів на основі 7-заміщених 3-тіазолілкумаринів для приєднання барвників до олігонуклеотидів та інших біомолекул. Ці реагенти включають 7-гідрокси-, 7-метокси- та 7-ацетоксипохідні 3-тіазоліл- і 3-(фенілтіазоліл)кумарину. Ключовими інтермедіатами синтезів були 7-гідроксипохідні відповідних кумаринів, що містять захищену карбоксиалкільну групу. 7-Метокси- та 7-ацетоксипохідні кумаринів і реагенти з вільною карбоксильною групою одержували комбінацією реакцій ацилювання чи метилювання й кислотного гідролізу. The synthesis of carboxyl derivatives of fluorescent probes based on 7-substituted 3-thiazolylcoumarins for the attachment of the dyes to oligonucleotides and other biomolecules is described. They include 7-hydroxy-, 7-methoxy and 7-acetoxy derivatives of 3-thiazolyl- and 3-(phenylthiazolyl)coumarin. The key intermediates in the synthesis were 7-hydroxy derivatives of corresponding coumarins containing protected carboxyalkyl group. Their synthesis was performed by condensing 2,4-dihydroxybenzaldehyde with two 2-(cyanomethyl)thiazoles containing ester function on an alkyl linker. Thiazole derivatives were in turn obtained by the condensation of cyanothioacetamide with corresponding α-haloketones. 7-Methoxy and 7-acetoxy coumarin derivatives and reagents with free carboxylic group were obtained by the combination of acylation, methylation and acidic hydrolysis reactions.